2023
DOI: 10.1136/ijgc-2022-003904
|View full text |Cite
|
Sign up to set email alerts
|

Role of minimally invasive secondary cytoreduction in patients with recurrent ovarian cancer

Abstract: ObjectiveRetrospective series have shown minimally invasive secondary cytoreductive surgery is a feasible approach in selected cases of recurrent ovarian cancer. However, no predictors of minimally invasive secondary cytoreductive surgery feasibility are currently available. This study aims to identify predictive factors of minimally invasive secondary cytoreductive surgery feasibility and to compare perioperative and survival outcomes in a matched series of recurrent ovarian cancer patients who underwent seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…For these reasons, surgical treatment assumes a crucial role. The repeated surgery for ILNR, even in platinum-sensitive ovarian cancer, remains an important tool and this has been confirmed by several previous studies which highlighted the prognostic benefit in those patients [ 13 , 14 , 15 , 22 , 26 , 28 ]. Diagnostic laparoscopy also plays an important role in identifying a more diffuse disease and preventing unnecessary laparotomies delaying the chemotherapy [ 29 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…For these reasons, surgical treatment assumes a crucial role. The repeated surgery for ILNR, even in platinum-sensitive ovarian cancer, remains an important tool and this has been confirmed by several previous studies which highlighted the prognostic benefit in those patients [ 13 , 14 , 15 , 22 , 26 , 28 ]. Diagnostic laparoscopy also plays an important role in identifying a more diffuse disease and preventing unnecessary laparotomies delaying the chemotherapy [ 29 ].…”
Section: Discussionmentioning
confidence: 57%
“…ILNR is actually considered as a rare entity in the context of EOC since it affects only 1–5% of relapsed EOC [ 16 , 17 ]. These ILNR has been described as a unique clinical disease entity, moreover, several studies underline a better prognosis in terms of PFS and OS compared to peritoneal or parenchymal forms of recurrence [ 20 , 23 , 24 , 25 , 26 ]. Furthermore, the idea that the lymph-node metastases in ovarian cancers are more chemoresistance has already been proposed by Morice et al in an analysis of 105 patients [ 27 ] and confirmed by several studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant chemotherapy at primary diagnosis, peritoneal and lymph-nodal pattern of recurrence, and single and oligometastatic disease at preoperative PET/CT scan were significantly correlated with MI-SCS feasibility. In the multivariate analysis, single disease (OR = 4.17, 95% CI: 1.83-9.53, p < 0.001) and oligometastatic disease at recurrence (OR = 3.46, 95% CI: 1.48-8.07, p = 0.004), neo-adjuvant chemotherapy at primary diagnosis (OR = 2.46, 95% CI: 1.27-4.78, p = 0.007), and lymph-nodal site (OR = 2.67, 95% CI: 1.09-6.53, p = 0.031) were confirmed to be independent predictors of MI-SCS [40]. They showed, for the first time, a surprisingly higher rate of neoadjuvant chemotherapy and interval debulking surgery (IDS) at first diagnosis (p = 0.030) in the MIS group.…”
Section: Patient Selectionmentioning
confidence: 85%
“…In this month's issue of International Journal of Gynecological Cancer, Conte et al 5 retrospectively evaluated the feasibility and survival outcomes in patients with recurrent ovarian cancer who underwent secondary cytoreduction via an open versus minimally invasive surgical approach. The authors included platinum sensitive patients with recurrent epithelial ovarian cancer and had preoperative positron emission tomography (PET)/computed tomography (CT) and diagnostic laparoscopy before embarking on the secondary cytoreduction.…”
mentioning
confidence: 99%